Influence of Exposure Cd1-xMgx Fe₂O4 Compound by RF Plasma (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:The work focuses on enhancing the structural properties, where the Cd1-x Mgx Fe2O4 products prepared by sol-gel solution were characterized. Auto ignition approach using several automated equipment, as FESEM, XRD, for concentrations (x=0.0,0.8 and 1), post-synthesis plasmas were exposed in a low-pressure chamber using the RF Magnetron Sputtering System and the results compared.  by X-ray diffraction analysis,  confirms the configuration to the FCC cubic structure of the studied samples. Plasma treatment did not affect the crystallization but the crystal size (D) of the particle size decreases after exposure to plasma from (32.33- 27.083)nm . Morphological studies confirmed surface shape changes and particle size reduction upon exposure to plasma. Materials and Methods:The sol-gel method common and old a chemical process for the production of a variety of nanostructures, most notably nanoparticles of metal oxide. In which The molecular feedstock is combined with water or alcohol and then subjected to moderate heating while being agitated.  The basic principle pertaining to the sol-gel technology is to manufacture a homogenous  solution created from raw materials also then gelatinized . The powders are ground and sintered in a refractory oven at 1100 ° C for 6 hours. The powder was then pressed by a hydraulic press at a pressure of 150 kN into molds to form a disc with a diameter of 20 mm. The work will take place in two phases: before exposing it to the plasma, and then when the samples are placed into the RF Magnetron Sputtering.Results:The X-ray measurements showed that the  un-exposure and plasma- exposure samples have a cubic spinel structure, and that the variation of the structural parameters with the exposure is irregular, Consequently enhancing the atoms' ability to diffuse after being put onto the substrate and grain size of the sample. The morphological analysis of the as-prepared ferrite Cd1-xMgxFe2O4 samples was performed using FE-SEM, which gives  details on the size and structure of the particles that make up the nanocrystals. The surface exposed to the plasma shows a change in the positions of the crystals and their cohesion with each other , which may result from a decrease in supermagnetic effect and lattice defects in Ferrite nanocrystalline films.Conclusion:The aim of this work is to synthesize Cd1-xMgx Fe₂O4 ferrite nanoparticles in spinel cube structure by sol-gel self-combustion method. Then, the synthesis of thermal plasma using Radio frequency (RF) plasma, where the structural properties, surface shape, and interpretation were studied properties of ferrite nanoparticles produced before and after plasma exposure. According to the conducted XRD investigations the validity of the cubic spinel structure of ferrite and that the irregular difference in the size of the crystals before and after the exposure, the particle size decreases after exposure to plasma from (32.33- 27.083)nm, and the capillary parameter they were reduced from (8.892 to 8.743)nm for plasma-treated samples.   the results obtained from shaping cubic spinel phase in both iron nanoparticles before and after plasma exposure supported by the XRD results. The morphological study revealed irregularity grain distribution and dominant agglomeration in ferrite before and after exposure.